A QUALITATIVE STUDY: SELF ESTEEM IN RELATION TO DATING VIOLENCE IMPACT - Ayu, Suci Musvita; Gustina, Erni; Sofiana, Liena; Puspita, Lukyana Dinar (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Negative self-esteem makes them vulnerable to becoming victims of Dating Violence (DV). Violence in dating is a worrying problem that arises in today's youth. The impact of those experiencing it also varies from mild to severe. This study aimed to analyze the impact of dating violence on adolescents in Yogyakarta. This is qualitative case study research. The research subjects were selected based on certain criteria, namely adolescents aged 18-24 years and women living in Yogyakarta who had experienced dating violence and had an impact on their psychology with a snowball sampling technique. The data collection technique used is structured in-depth interviews. The research instrument used was an interview guide to key informants and triangulation to informants' friends. The validity test was carried out through source triangulation. The two informants experienced psychological violence in their dating relationship in the form of an easily angry partner, berated, excessively jealous, limiting the relationships, manipulative, and prohibited from looking attractive and taking care of themselves. These forms of psychological violence impact self-esteem, such as the emergence of a sense of insecurity, liking to compare, always feeling like a failure, low self-esteem, interfering with daily activities, and causing trauma for both informants. Psychological violence in dating received by the two informants impacts their self-esteem.